LEADERSHIP SUCCESSION IN PESANTREN - Aedi, Nur (Jurnal Pendidikan Islam, 2016)
This paper aims to explain leadership succession in one of Indonesian Islamic educational institution, specifically in salafiyah pesantren. Scope of this paper covered a system of pesantren leadership succession. Method of analysis was literature of pesantren from Mastuhu. The discussion revealed that a tradition of pesantren leadership succession was influenced by heredity, idealism, and respect as well as fanaticism to kiai. Traditionally, other people will not be in line with the ideology of pesantren’s founders. Pesantren will being closed down to kiai. Santries as asuccessors are kiai’s struggle and will be turn in when a successor act as founder. Pesantren will be let it in order to be better than before. For pesantren, other people are not successors of kiai’s struggles. It had a serious impact on sustainability and development of Islamic educational institution in the future as communities. Pesantren as communities are factor of determinant to sustain of Indonesian Islamic educational to survive in global society. So, Indonesian government has to supported to develop pesantren. Government could establish specific director general of pesantren in national education. Comprehensively, Islamic educational institutions something like pesantrens should be accommodate and respond to global issues.